Mr. Inbetween. The complete first season [videorecording (DVD)] - Ryan, Scott (Writer on television); Ryan, Scott (Writer on television); Herriman, Damon, 1970-; Rosniak, Justin (20th Century Fox Home Entertainment, 2019)
Juggling a new relationship, parental responsibilities, friendship, and a sick brother while earning a living would be difficult for anyone, but it's particularly tricky as a hitman. Ray Shoesmith (Scott Ryan) takes care of people, collecting debts, relieving them of drugs and guns, and often taking care of them permanently. Ray demands respect and does not tolerate anyone who doesn't live up to his very strong and very clear code of ethics. The few he trusts, he'll do anything for.